Effect of twin square tunnels on ground acceleration responses during earthquakes - Ong, Jun Ping (Nanyang Technological University, 2020)
Past studies have shown that the presence of underground tunnels results in an amplification to the ground responses. This project is a study on the effects of twin square tunnels on the ground responses under seismic loading. Parametric analysis is conducted using PLAXIS 2D, a finite element software, and the effects of varying tunnel size and depth are investigated. Peak ground acceleration (PGA) values of the ground responses were chosen for analysis, to simulate the most critical ground responses. A soil model of 720m width by 100m height is chosen for the simulation. Twin square tunnels are then constructed in the centre of the soil model, within an 80m loose sand layer lying above 20m of granite bedrock. Earthquake acceleration data from the 2014 Ferndale, California earthquake was used as the input for seismic loading. Tunnel depths of 16m, 32m, 48m and 64m were used in the simulation. Subsequently, further simulations on tunnel size were conducted, with tunnel size of 3m, 6m, 9m and 12m. The results of the simulations showed that the presence of twin square tunnels resulted in an amplification of PGA values recorded on the ground surface. Moreover, greater amplification of ground surface PGA was observed when increasing tunnel depth. Increasing the tunnel sizes up to 9m, leads to a similar increase in amplification.